2023
DOI: 10.1136/bmj-2022-072638
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalising community engagement for quality of care: moving beyond the rhetoric

Brynne Gilmore,
Paul Henry Dsane-Aidoo,
Mikey Rosato
et al.

Abstract: Community engagement has the potential to improve quality of care but is poorly represented in policy and the literature; its institutionalisation in health systems must be supported, argue Brynne Gilmore and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Health care users need to be continuously engaged in the QOC dialogue. The Network countries have demonstrated that this can happen when there is a deliberate process and platforms for engaging them ( 32 , 39 ). However, we are still at the early stages of understanding the mechanisms needed to sustain this engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care users need to be continuously engaged in the QOC dialogue. The Network countries have demonstrated that this can happen when there is a deliberate process and platforms for engaging them ( 32 , 39 ). However, we are still at the early stages of understanding the mechanisms needed to sustain this engagement.…”
Section: Discussionmentioning
confidence: 99%
“…However, we are still at the early stages of understanding the mechanisms needed to sustain this engagement. Countries such as Malawi and Ghana have set up structures to strengthen the engagement of communities, but the functionality of these structures has been a challenge, and require further attention to be fully operational and sustained ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, closer than that, recognizing the former should be based on three dimensions: the temporal clinical practice following a continually updated clinical guideline [ 57 ], the spatial variation of the patient demographics [ 58 – 60 ], and the infinitely varied efficiencies of hospital operational systems [ 61 , 62 ]. The first raises a requirement on the prospective validation of prediction models and endows the prediction model with a remarkable valid period [ 57 , 63 ].…”
Section: Represent Accurately and Integrate Into Clinical Practice Se...mentioning
confidence: 99%
“…These mechanisms, often driven by the health system, aim to ensure users’ participation and demonstrate accountability of health services. Examples include the community scorecards in Ethiopia and Ghana, which are co-developed and jointly implemented with communities 89…”
Section: People Centred Carementioning
confidence: 99%
“…Examples include the community scorecards in Ethiopia and Ghana, which are co-developed and jointly implemented with communities. 8 9…”
Section: People Centred Carementioning
confidence: 99%